Risk-Based Premiums for Pension Insurance - Zurita L., Salvador (Estudios de Administración, 1996)
The present paper develops a model to compute risk-based premiums for the USA pension insurance administered by the public Pension Benefit Guaranty Corporation (PBGC). Pension insurance is shown to he analogous to a financial put option, and pricing equations and their analytical solutions are obtained. The model includes costly audits that follow a Poisson process, whose average frequency is determined by the policymaker in order to attain Pareto-optimality. The model is estimated for a sample of us firms for the period ¡982-1986. The main policy implication is that risk-based premium rates increase at an increasing rate with the level of underfunding, in contrast with the current law of flat premium rates after certain level of underfunding.